Ionic Liquids as Efficient Extractants for Quercetin from Red Onion (Allium cepa L.) - Domanska, Urszula; Wisniewska, Anna; Dabrowski, Zbigniew; Wieckowski, Mikolaj (Journal of Applied Solution Chemistry and Modeling, 2018)
The solubility of Quercetin in alcohols, esters and in 1-ethyl-3-methylimidazolium trifluoroacetate, [EMIM][TFA] ionic liquid (IL) using the dynamic method was measured at constant pH in a range of temperature 233-373 K and compare to the literature data. The experimental solubility data have been correlated by means of commonly known GE models,UNIQUAC and NRTL with the assumption that the systems studied here present simple eutectic behaviour. The basic thermal properties of Quercetin, i.e., fusion temperature and the enthalpy of fusion have been measured with differential scanning microcalorimetry technique (DSC).The application of alcohols, esters and ionic liquids (ILs) as alternatives to conventional organic solvents in the liquid-liquid extraction of Quercetin from different medicinal plants, flowers and frozen red onion (Allium cepa L.) was investigated. The parameters affecting the extraction yield using ILs such as chemical structures of the IL cation and anion, the phase volume ratio of extracting solvent, time of extraction and the Quercetin form of sample and concentration were evaluated. Specific Quercetin composition was performed through HPLC measurements. Using the most effective ILs in extraction, the 14.3±0.1g.kg-1 and 5.9±0.1g.kg-1of Quercetin from frozen pure red onion was obtained with N,N-diethyl-N-methyl-N-(2-methoxyethyl)ammonium tetrafluoroborate, [N2,2,1,2OCH3][BF4] and 1-ethyl-3-methylimidazolium trifluoroacetate, [EMIM][TFA], respectively.